CONSTRAINTS OF GEOGRAPHY TEACHER OF SMA N 1 NGAGLIK IN DEVELOPING THE 2013 CURRICULUM LEARNING DEVICES IN SLEMAN REGENCY - Fajar Agung Nugroho; H Hastuti (Department of Geography Education, University of Jember, 2019)
This study aims to determine: (1) the difficulties of geography teachers in SMA N 1 Ngaglik to develop learning media, and (2) how to solve those difficulties. This research was conducted in SMA N 1 Ngaglik. This study used descriptive qualitative method. The subjects in this study were the geography teachers. The data collection techniques used was observation, interviews, and documentation. The data analysis technique in this study used interactive analysis which includes data collection, data reduction, data presentation, and conclusion. The results of this study indicate: (1) the obstacles found in the school like the teachers develop syllabus using a scientific approach only, they have not carried out all learning models in accordance with Curriculum 2013, the difficulties in developing learning media, the difficulties in developing learning media, and the difficulties in assessing balanced attitudes and skills with knowledge, and (2) to solve those difficulties the teacher carries out various ways by discussing and sharing with other geography teacher, participates in MGMP activities from the school to the district level, attends trainings or workshops to add insight and various information for the improvements in developing learning media. Keywords: obstacles, learning media, curriculum 2013 References Cheung, A.C.K & Wong, P.M. (2012). â€œFactors Affecting the Implementation of Curriculum Reform in Hong Kong: Key Findings from a Largeâ€Scale Survey Studyâ€. International Journal of Educational Management, Vol. 26 Iss: 1, pp.39 â€“ 54. Doi: http://dx.doi.org/10.1108/09513541- 211194374. Eraslan, A. (2013). â€œTeachersâ€™ Reflections on the Implementation of the New Elementary School Mathematics Curriculum in Turkeyâ€. HU Journal of of Education. 28 (2), 152-165. Mulyasa. E (2014). Pengembangan dan Implementasi kurikulum 2013. Bandung: PT. Remaja Rosdakarya. Kankam, B., Bordoh, A., Eshum, I., Bassaw, T.K, & Korang, F.Y. (2014). â€Teachersâ€™ Perception of Authentic Assessment Techniques Practice in Social Studies Lessonsin Senior High Schools in Ghanaâ€. International Journal of Educational Researchand Information Science. 1 (4): 62-68. Katuuk, D.A. (2014). Manajemen Implementasi Kurikulum: Strategi Penguatan Implementasi Kurikulum 2013. Cakrawala Pendidikan, 13 (1): 13-26. Kurebwa, M. & Nyaruwata, L.T. 2013. â€Assessment Challenges in the Primary Schools: A Case of Gweru Urban Schoolsâ€. Greener Journal of Educational Research 3(7), pp. 336-344. Lumadi, M.W. (2013). â€œChallenges Besetting Teachers in Classroom Assessment: An Exploratory Perspectiveâ€. Journal of Social Science. 34 (3): 211-221. Mayer, V.J. & Fortner, R.W. (1987). â€œRelative Effectiveness of Four Modes of Dissemination of Curriculum Materialsâ€, TheJournal of Environmental Education, 19(1) 25-30. Doi:10.1080/00958964.1987.- 10801957. Menteri Pendidikan dan Kebudayaan Republik Indonesia. (2013). Peraturan Menteri Pendidikan dan Kebudayaan Nomor 81 Tahun 2013 tentang Pelaksanaan Penilaian. Menteri Pendidikan dan Kebudayaan Republik Indonesia. 2014. Peraturan Menteri Pendidikan dan Kebudayaan Nomor 104 Tahun 2014 tentang Pelaksanaan Penilaian. Ryder, J., Banner, I., & Homer, M. (2014). â€œTeachersâ€™ Experiences of Science Curriculum Reformâ€. School. Sugiyono. (2007). Metode Penelitian Kuantitatif Kualitatif dan R & D. Bandungan: Alfabeta. Sukardi. (2005). Metodologi Penelitian Pendidikan Kompetensi dan Praktiknya. Jakarta: Bumi Aksara. Syomwene, A. (2013). â€œFactors Affecting Teachersâ€™ Implementation of Curriculum Reforms and Educational Policies in Schools: The Kenyan Experienceâ€. Journalof Education and Practice. 4 (22) 80- 86. Wina Sanjaya. (2010). Perencanaan & Desain Sistem Pembelajaran. Jakarta: Kencana. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License